(3GdeMGSHI h JMdjd GdbhGFe GdeGdjIs - (3eMeO YHGS(B, (3HOhjs ((3GdGRQjWI(B:s (3GdecJH GdLGeYj GdMOjK(B,s)
(3WHjYI GdeMGSHI cfXGe ddeYdheGJ h JTZjd GdfXGe GdeMGSHj , GdeMGSHI aj GdeTQhY GdJLGQj hGdeTQhY GdUfGYj h CNjQG GSJbQGA h JMdjd GdbhGFe GdeGdjI eY hLhO CSFdI h JWHjbGJ aj fgGjI cd aUd (B.s
((3GbJfGAGJ (B2014 3(3f(B)s
Keywords: (3GdJMdjd GdeGdjs; (3GdeMGSHIs